Teacher professionalism: Opportunities and challenges in the education delivery system - Viggy Anggini (12 Waiheru, 2024)
The study set out to characterize the professionalism of teacher preparation programs offered by Islamic schools and institutions. This kind of research combines a review of the literature with qualitative methods. They gather data by locating and compiling information from various sources, including books, journals, and previous studies. Meanwhile, data analysis was done using data triangulation techniques, member checking, and auditing, as well as Miles & Huberman's data analysis methodologies, which include data reduction, data display, and conclusions. The professionalism of teachers is a good indicator of the quality of education, according to research findings. Several activities are conducted to enhance teacher professionalism, such as workshops, seminars, M.G.M.P., and training. They are improving the calibre of teachers by organizing, carrying out, and monitoring changes. Professional teachers in schools are beneficial in improving the quality of education, one of which is by conducting training related to experienced teachers in schools. Skilled teachers are applied by meeting the tools of teaching needs, attendance, making academic calendars, and having work meetings with other teachers. They are also proven by attending professional teacher improvement training in schools. Teachers must be competent to carry out the learning process utilizing the current I.T. systems since teacher professional education presents both opportunities and obstacles. Teacher quality is achieved by mastering learning supported by understanding their duties and responsibilities.